A Lean Manufacturing Model - Sinnasamy, Balamurugan (2005)
Lean Manufacturing is an operational tool that had been successfully used by some companies in the past to improve manufacturing efficiency and reduce cost. The main philosophy of lean manufacturing is to eliminate ‘waste’ from manufacturing and with that, improve efficiency of operational resources.